Case Study: Language Differences in the Challenges of New Students Adapting to the Indonesian University of Education Environment - Wulanda, Agiva Early; Putri, Hariza Adia; Almudhia, Salisa; Azizah, Sarah Nur; Komariah, Siti; Supriyono, Supriyono (JUPE : Jurnal Pendidikan Mandala, 2024)
This study examines the problems that exist in new students of Universitas Pendidikan Indonesia regarding the problems of some Universitas Indonesia students from minority ethnic groups who have difficulty adapting because the language of instruction used is different from the language they use daily in their area. This research has the aim that we as students, both migrants and local students, know the differences in regional languages and also everyday languages that have an impact on adapting and how to deal with these problems. The research method we use is the Kulialitatif method with interview techniques and literature studies. The location of this research was conducted at the Indonesian Education University with new students as informants consisting of different tribes.